How heavy is the medical expense burden among the older adults and what are the contributing factors? A literature review and problem-based analysis - Chen, Jie; Zhao, Meizhen; Zhou, Renyi; Ou, Wenjing; Yao, Pin (Frontiers in Public Health, 2023)
In recent years, the aging population and increasing medical expenses among the older adults have emerged as significant public health concerns. National governments must conduct medical expense accounting and implement measures to reduce the burden of medical costs on the older population. However, limited studies have focused on total medical expenditure from a macro perspective, with many researches exploring individual medical expenses from different perspectives. This review introduces the trend of population aging and its impact on health cost change, reviews research on the medical expense burden of the older population and contributing factors, and points out underlying problems and limitations of current studies. Based on the present studies, the review emphasizes the necessity of medical expense accounting and analyzes the medical expense burden of the older population. Future studies should explore the impacts of medical insurance funds and health service system reforms on reducing medical expenses and developing a supporting medical insurance reform plan.